Turning the Mirror on the Architects: A Study of the Open-Plan Office and Work Behaviors at an Architectural Company - Węziak-Białowolska, Dorota; Dong, Zhao; McNeely, Eileen (Frontiers in Psychology, 2018)
Following the rising cost of real estate and a desire to increase collaboration and communication among employees, open-plan office has been trending over the past decades. Research about the human impact of open-plan office is equivocal in endorsing this trend. The mixed results are further cofounded following the specific job requirements, such as the need for privacy in jobs requiring a high level of concentration or – in contrast – the need for open workspace in jobs benefitting from team work and knowledge sharing. This study aims to understand the relationship between perceptions of three characteristics of open-plan office (acoustical privacy, visual privacy, office density) and the impact they yield on employees’ judgement- as well as the affect-driven behaviors. The study benefits from data from 456 employees located in 20 regional office locations within the same architectural firm. The restriction to employees of a design firm enables examinations of participants who are already sensitive to the impacts of space by the nature of their work. Variables of interest included employee perception of the workspace (privacy, office density, fit to workspace), employee rating of social relationships, self-reported mood (irritability) and optimal functioning (number of limited ability days) and work impacts (job satisfaction, work engagement and job performance). Model of behavior in open-plan office setting based on affective events theory is adopted. Mediation roles of irritability and perception of fit to workspace are examined. Our results show that working in the open-plan office limits the experience of privacy and intensifies perception of intrusion among employees of an architectural company, mostly architects and designers. Additionally, employees’ perception of lack of privacy and high office density negatively affects job satisfaction, work engagement and internal work relation as well as increases number of limited ability days. Interestingly, the lack of privacy and high office density seem to positively affect expressive personal relations among coworkers and job performance. We find supporting evidence for mediation roles of negative emotions, i.e. irritability and perception of fit to workspace.